Comparative Analysis of the Tourism Sector on Poverty with GRDP - Siti Eha; Prajanti, Sucihatiningsih Dian Wisika (Efficient: Indonesian Journal of Development Economics, 2024)
The tourism sector is one of the largest and fastest growing sectors in the world that can boost the economy, create new jobs and reduce poverty. The provinces of DI Yogyakarta and Central Java have the highest percentage of poor people in Java and are provinces with leading tourism sectors that can compete at the world level. This study aims to determine and analyze the effect of the tourism sector on the number of poor people through GRDP as an intervening variable in 2012-2022. This research is a type of quantitative research with the Path Analysis research method. The results showed that: (1) The number of tourist attractions has a positive and significant effect on GRDP in Central Java and DI Yogyakarta.  (2) The number of hotel rooms has a positive and significant effect on GRDP in Central Java and Yogyakarta.  (3) GRDP has a negative and significant effect on the number of poor people in Central Java and Yogyakarta.